НАРОДНЫЕ МУЗЫКАЛЬНЫЕ ИНСТРУМЕНТЫ (ART AND CULTURE BULLETIN, 2024)
(ranges of folk instruments) origin of folk instruments.
Keywords: folk instruments; plector group; (dutar, rubab, Avgan rubab); percussion instruments; (doira, chang, nagora, wind instruments nai, koshnai, surnai).